EVALUATION OF RISK FACTORS AND EXPENDITURE ASSOCIATED WITH ACUTE DIARRHEA IN UNDER-FIVE CHILDREN - THAKAN, SOMYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Poor socioeconomic level, an unsanitary living environment, and the caregiver’s behavior are all associated with the severity of childhood diarrhea. The goal of this study is to identify the risk factors and financial costs related to diarrhea in children under the age of five. Methods: Between July 2021 and March 2022 , a convenience sampling case -control research with 210 cases and 210 controls was conducted in Jhalawar. Results: Diarrhea was linked to younger caretakers, a lack of formal education, a lack of awareness, merely washing hands with water, and quitting nursing. Poor economic position, having a family of five or more, being crowded, having a domestic animal, drinking unsafe water, not having a hygienic toilet, disposing of rubbish in an unhealthy manner, and eating street vendor cuisine are all linked to diarrhea. Conclusion: Out of pocket, expenditure and risk factors for diarrhea under 5 years of age are still present in Jhalawar.